Ex-ante Assessment of Urban Development Projects - Buzási, Attila; Szalmáné Csete, Mária (European Journal of Sustainable Development, 2017)
Budapest, the capital of Hungary facing several climatic challenges in the next decades, therefore there is a need of sustainable development projects with strong emphasis on the projected impacts of climate change. The main aim of the paper is to evaluate an ex-ante assessment methodology to analyse existence or absence of sustainability principles in renewal projects. The selected works have a focus on the same challenge, namely building an intermodal passenger transport hub and renewing the surrounding area in the district IV. of Budapest. The renewal plans have been developed by students from different Hungarian universities during a three-day-workshop. However the main focus of the workshop was on tackling the transport-based challenges, most of the elaborated plans have strong emphasis on green and blue areas, communities, building and related sustainability issues. The jury of the competition included mainly transportation engineers, real estate developers and civil engineers, therefore there is a need of involving broader sustainability and climate-related aspects into the assessment process. The output of the paper shall reveal the differences between developer-oriented ranking and the climate-related one regarding the same urban renewal challenge. Keywords: urban sustainability; climate change; urban planning; ex-ante